New synchrotron powder diffraction facility for long‐duration experiments. Issue 1 (27th January 2017) - Murray, Claire A.; Potter, Jonathan; Day, Sarah J.; Baker, Annabelle R.; Thompson, Stephen P.; Kelly, Jon; Morris, Christopher G.; Yang, Sihai; Tang, Chiu C.
Abstract : The world's first dedicated synchrotron instrument for long‐duration experiments has been built and commissioned at Diamond Light Source. The new beamline I11 user facility is designed for the study of slow kinetics in polycrystalline materials. Abstract : A new synchrotron X‐ray powder diffraction instrument has been built and commissioned for long‐duration experiments on beamline I11 at Diamond Light Source. The concept is unique, with design features to house multiple experiments running in parallel, in particular with specific stages for sample environments to study slow kinetic systems or processes. The instrument benefits from a high‐brightness X‐ray beam and a large area detector. Diffraction data from the commissioning work have shown that the objectives and criteria are met. Supported by two case studies, the results from months of measurements have demonstrated the viability of this large‐scale instrument, which is the world's first dedicated facility for long‐term studies (weeks to years) using synchrotron radiation.